2D/2D 1T‐MoS2/Ti3C2 MXene Heterostructure with Excellent Supercapacitor Performance. (20th February 2020) - Wang, Xin; Li, Han; Li, Hui; Lin, Shuai; Ding, Wei; Zhu, Xiaoguang; Sheng, Zhigao; Wang, Hai; Zhu, Xuebin; Sun, Yuping
Abstract: 2D/2D heterostructures can combine the collective advantages of each 2D material and even show improved properties from synergistic effects. 2D Transition metal carbide Ti3 C2 MXene and 2D 1T‐MoS2 have emerged as attractive prototypes in electrochemistry due to their rich properties. Construction of these two 2D materials, as well as investigation about synergistic effects, is absent due to the instability of 1T‐MoS2 . Here, 3D interconnected networks of 1T‐MoS2 /Ti3 C2 MXene heterostructure are constructed by magneto‐hydrothermal synthesis, and the electrochemical storage mechanisms are investigated. Improved extra capacitance is observed due to enlarged ion storage space from a synergistically interplayed effect in 3D interconnected networks. Outstanding rate performance is realized because of ultrafast electron transport originating from Ti3 C2 MXene. This work provides an archetype to realize excellent electrochemical properties in 2D/2D heterostructures. Abstract : Improved extra capacitance is observed due to enlarged ion storage space from a synergistically interplayed effect in 1T‐MoS2 /Ti3 C2 MXene 3D interconnected networks. Outstanding rate performance is realized due to ultrafast electron transport originating from Ti3 C2 MXene. This work paves the way for investigating the electrochemical energy storage mechanism of supercapacitors in 2D/2D heterostructures.